Diskursus Tafsir Teologis Ulama Nusantara dan Transnasional (Studi Kritis Tafsir Asy’ariyyah dan Wahabi di Indonesia) - Alim, Khozinul; Hude, Muhammad Darwis; Hasyim, Arrazy (Al Furqan: Jurnal Ilmu Al Quran dan Tafsir, 2024)
This study discusses the theological conflict arising from interpretational differences between Nusantara Ulama and Transnational Ulama in Indonesia. The researcher analyzes the paradigms and mainstream interpretations of the two Islamic typologies that have developed in Indonesia, namely Nusantara Ulama and Transnational Ulama. The author also seeks to identify points of difference and initiate an integrative effort to minimize existing tensions. Using a qualitative approach with library research as the primary reference and employing a comparative tafsir method as an analytical tool, this study also adopts the approach of ilm al-kalam (theology). The research findings indicate that the Nusantara Ulama paradigm tends to use a contextual paradigm with a mainstream interpretation of substantialist tafsir, while the Transnational Ulama uses a textual paradigm with a mainstream interpretation of scripturalist tafsir. These differences in paradigm and mainstream interpretation often lead to misunderstandings, even accusations of heresy or disbelief towards each other, despite the essential similarities in their views. To minimize ideological conflict regarding the interpretation of theological verses, the author proposes an integrative approach through convergent interpretation (tafsīr mutaqāribah). This approach represents a compromise between substantialist and scripturalist tafsir. This tafsir model offers a peaceful way to reach a mutual agreement that both sides can accept. The interpretation focuses on the core teachings of the Qur'an concerning theological verses, with consideration for maslahat (public interest), by finding common ground amidst the various interpretations. This approach requires mufassirs to socialize the meaning of theological verses to the Muslim community. Mufassirs need to re-recognize the primary purpose of the Qur'an's revelation to Prophet Muhammad, which is to bring a mission of peace, while also reconciling diverse opinions with a firm adherence to the essential theological teachings of Islam and upholding the Qur'an and Sunnah.